Perlindungan Hukum Bagi Pengguna Kosmetik Perawatan Kulit Berlabel Bpom Palsu Ditinjau Dari Peraturan Badan Pengawas Obat Dan Makanan Nomor 23 Tahun 2019 Tentang Persyaratan Teknis Bahan Kosmetik - Elsa Novianti Saputri; Eka Jaya Subadi (Private Law, 2022)
This study aims to determine the legal protection for cosmetic users labeled BPOM when viewed from BPOM Regulation Number 23 of 2019, to determine BPOM's responsibility for cosmetic products with fake labels circulating in the community. The type of research used is normative legal research with an approach method that is a conceptual approach and a statutory approach, sources and types of legal materials in the form of library materials consisting of primary, secondary, and tertiary legal materials. The results of this study are the forms of legal protection for cosmetic users: Preventive Protection, Repressive Protection, and Rehabilitation. BPOM's responsibilities for cosmetics with fake labels: BPOM conducts supervision, recalls cosmetic products and provides legal sanctions. It is concluded that the legal protection for cosmetic users is in accordance with BPOM Regulation No. 23 of 2019. The author's suggestion is that the public must be wise in using cosmetic products.